Nonlinear finite element analysis of masonry wall strengthened with CFRP strips. (3rd March 2016) - Alyavuz, Bahadir; Anil, Özgür; Bulut, Nalan
Abstract : In many experimental studies, it has been proved that unreinforced masonry (URM) brick walls have high strength against lateral forces acting in plane. However, out-of-plane strength of URM brick walls against lateral forces has found to be quite low. According to the experiences that were obtained from the major earthquakes, the low out-of-plane performance of URM brick walls resulted in excessive loss of human lives during an earthquake, hence the strengthening of URM brick walls with CFRP strips has been appeared to be a very important subject. However, very limited literature has been found. Especially, the data obtained from experimental studies must be increased for the true understanding of the behavior of strengthened brick walls under out-of-plane lateral forces. However, in most cases, this procedure required large number of expensive experiments. At this stage, numerical analysis can be an appropriate choice, thus in this paper a finite element model is presented for modeling URM brick walls that are strengthened with CFRP strips. The numerical results are compared with the experimental ones and consistent results are obtained from the finite element model. General purpose finite element analysis software ANSYS is used throughout this study. Contact elements are used along the masonry wall–CFRP strip interfaces for the investigation of the stress distribution and load – strain behavior.